# SPECIAL PRODUCTS OF BINOMIALS

Special products are easier ways to find the product of two binominals than multiplying each term in the first binomial with all terms in the second binomial.

## Finding the Products in the Form (a + b)²

Imagine a square with sides of length (a + b). The area of this square is (a + b)(a + b), or (a + b)2. The area of this square can also be found by adding the areas of the smaller squares and rectangles inside.

The sum of the areas inside is

a2 + ab + ab + b2

This means,

(a + b)2  =  a2 + 2ab + b2

The FOIL method can be used to verify this. A trinomial of the form a2 + 2ab + bis called a perfect-square trinomial. A perfect-square trinomial is a trinomial that is the result of squaring a binomial.

Example 1 :

Multiply.

(x + 5)2

Solution :

Use the rule for (a + b)2

(a + b)2  =  a2 + 2ab + b2

Identify a and b : a = x and b = 5.

(x + 5)2  =  x2 + 2(x)(5) + 52

=  x2 + 10x + 25

Example 2 :

Multiply.

(2x + 3y)2

Solution :

Use the rule for (a + b)2

(a + b)2  =  a2 + 2ab + b2

Identify a and b : a = 2x and b = 3y.

(2x + 3y)2  =  (2x)2 + 2(2x)(3y) + (3y)2

=  4x2 + 12xy + 9y2

Example 3 :

Multiply.

(3 + z2)2

Solution :

Use the rule for (a + b)2

(a + b)2  =  a2 + 2ab + b2

Identify a and b : a = 3 and b = z2

(3 + z2)2  =  (3)2 + 2(3)(z2) + (z2)2

=  9 + 6z2 + z4

Example 4 :

Multiply.

(-y + 3)2

Solution :

Use the rule for (a + b)2

(a + b)2  =  a2 + 2ab + b2

Identify a and b : a = -y and b = 3.

(-y + 3)2  =  (-y)2 + 2(-y)(3) + (3)2

=  y2 - 6y + 9

## Finding the Products in the Form (a - b)²

The FOIL method can be used to find products in the form (a - b)2. A trinomial of the form a2 - 2ab + bis also a perfect-square trinomial, because it is the result of squaring the binomial (a - b)2.

Example 1 :

Multiply.

(x - 4)2

Solution :

Use the rule for (a - b)2

(a - b)2  =  a2 - 2ab + b2

Identify a and b : a = x and b = 4.

(x - 4)2  =  x2 - 2(x)(4) + 42

=  x2 - 8x + 16

Example 2 :

Multiply.

(6y - 1)2

Solution :

Use the rule for (a - b)2

(a - b)2  =  a2 - 2ab + b2

Identify a and b : a = 6y and b = 1.

(6y - 1)2  =  (6y)2 - 2(6y)(1) + 12

=  36y2 - 12y + 1

Example 3 :

Multiply.

(3c - 4d)2

Solution :

Use the rule for (a - b)2

(a - b)2  =  a2 - 2ab + b2

Identify a and b : a = 3c and b = 4d.

(3c - 4d)2  =  (3c)2 - 2(3c)(4d) + (4d)2

=  9c2 - 24cd + 16d2

Example 4 :

Multiply.

(3 - m2)2

Solution :

Use the rule for (a - b)2

(a - b)2  =  a2 - 2ab + b2

Identify a and b : a = 3 and b = m2

(3 - m2)2  =  (3)2 + 2(3)(m2) + (m2)2

=  9 + 6m2 + m4

## Finding the Products in the Form (a + b)(a - b)

An area model can be used to see that

(a + b)(a - b)  =  a2 - b2

Step 1 :

Begin with a square with area a2. Remove a square with area of b2. The area of the new figure is a2 - b2. Step 2 :

Then remove the smaller rectangle on the bottom. Turn it side it up next to the top rectangle. Step 3 :

The new arrangement is a rectangle with length (a + b) and width (a - b). Its area is (a + b)(a - b). So (a + b)(a - b)  =  a2 - b2

A binomial of the form a2 - b2 is called a difference of two squares.

Example 1 :

Multiply.

(x + y)(x - y)

Solution :

Use the rule for (a + b)(a - b).

(a + b)(a - b)  =  a2 - b2

Identify a and b : a = x and b = y.

(x + y)(x - y)  =  x2 - y2

Example 2 :

Multiply.

(y + 5)(y - 5)

Solution :

Use the rule for (a + b)(a - b).

(a + b)(a - b)  =  a2 - b2

Identify a and b : a = y and b = 5.

(y + 5)(y - 5)  =  y2 - 52

=  y2 - 25

Example 3 :

Multiply.

(p2 + 2q)(p2 - 2q)

Solution :

Use the rule for (a + b)(a - b).

(a + b)(a - b)  =  a2 - b2

Identify a and b : a = p2 and b = 2q.

(p2 + 2q)(p2 - 2q)  =  (p2)2 - (2q)2

=  p4 - 4q2

Example 4 :

Multiply.

(8 + m)(8 - m)

Solution :

Use the rule for (a + b)(a - b).

(a + b)(a - b)  =  a2 - b2

Identify a and b : a = 8 and b = m.

(8 + m)(8 - m)  =  (8)2 - (m)2

=  64 - m2

## Problem-Solving Application

Example :

A square koi pond is surrounded by a gravel path. Write an expression that represents the area of the path. Solution :

Understand the Problem

The answer will be an expression that represents the area of the path.

List the important information :

(i) The pond is a square with a side length of (x - 3).

(ii) The path has a side length of (x + 3).

Make a Plan

The area of the pond is (x - 3)2. The total area of the path plus the pond is (x + 3)2. You can subtract the area of the pond from the total area to find the area of the path.

Solve

Step 1 :

Find the total area.

Use the rule for (a + b)2

(a + b)2  =  a2 + 2ab + b2

Identify a and b : a = x and b = 3.

(x + 3)2  =  (x)2 + 2(x)(3) + (3)2

=  x2 + 6x + 9

Step 2 :

Find the area of the pond.

Use the rule for (a - b)2

(a - b)2  =  a2 - 2ab + b2

Identify a and b : a = x and b = 3.

(x - 3)2  =  (x)2 - 2(x)(3) + (3)2

=  x2 - 6x + 9

Step 3 :

Find the area of the path.

Area of Path  =  Total Area - Area of Pond

=  (x2 + 6x + 9) - (x2 - 6x + 9)

Use the Distributive Property.

=  x2 + 6x + 9 - x2 + 6x - 9

Group like terms together.

=  (x2 - x2) + (6x + 6x) + (9 - 9)

Combine like terms.

=  12x

The area of the path is 12x.

## Special Products of Binomials

Perfect-Square Trinomials :

(a + b)2  =  (a + b)(a + b)  =  a2 + 2ab + b2

(a - b)2  =  (a - b)(a - b)  =  a2 - 2ab + b2

Difference of Two Squares :

(a + b)(a - b)  =  a2 - b2 Apart from the stuff given above, if you need any other stuff in math, please use our google custom search here.

If you have any feedback about our math content, please mail us :

v4formath@gmail.com

You can also visit the following web pages on different stuff in math.

WORD PROBLEMS

Word problems on simple equations

Word problems on linear equations

Algebra word problems

Word problems on trains

Area and perimeter word problems

Word problems on direct variation and inverse variation

Word problems on unit price

Word problems on unit rate

Word problems on comparing rates

Converting customary units word problems

Converting metric units word problems

Word problems on simple interest

Word problems on compound interest

Word problems on types of angles

Complementary and supplementary angles word problems

Double facts word problems

Trigonometry word problems

Percentage word problems

Profit and loss word problems

Markup and markdown word problems

Decimal word problems

Word problems on fractions

Word problems on mixed fractrions

One step equation word problems

Linear inequalities word problems

Ratio and proportion word problems

Time and work word problems

Word problems on sets and venn diagrams

Word problems on ages

Pythagorean theorem word problems

Percent of a number word problems

Word problems on constant speed

Word problems on average speed

Word problems on sum of the angles of a triangle is 180 degree

OTHER TOPICS

Profit and loss shortcuts

Percentage shortcuts

Times table shortcuts

Time, speed and distance shortcuts

Ratio and proportion shortcuts

Domain and range of rational functions

Domain and range of rational functions with holes

Graphing rational functions

Graphing rational functions with holes

Converting repeating decimals in to fractions

Decimal representation of rational numbers

Finding square root using long division

L.C.M method to solve time and work problems

Translating the word problems in to algebraic expressions

Remainder when 2 power 256 is divided by 17

Remainder when 17 power 23 is divided by 16

Sum of all three digit numbers divisible by 6

Sum of all three digit numbers divisible by 7

Sum of all three digit numbers divisible by 8

Sum of all three digit numbers formed using 1, 3, 4

Sum of all three four digit numbers formed with non zero digits

Sum of all three four digit numbers formed using 0, 1, 2, 3

Sum of all three four digit numbers formed using 1, 2, 5, 6

Featured Categories

Math Word Problems

SAT Math Worksheet

P-SAT Preparation

Math Calculators

Quantitative Aptitude

Transformations

Algebraic Identities

Trig. Identities

SOHCAHTOA

Multiplication Tricks

PEMDAS Rule

Types of Angles

Aptitude Test 